Climatic and Environmental History of Isla de los Estados, Argentina - Ponce, Juan Federico; Fernández, Marilén
Isla de los Estados (Staten Island) is located in the extreme south of South America. It has been described by numerous mariners who have visited it at different times since 1616, categorizing it as one of the most inhospitable but spectacular islands in the world. It is separated by a distance of 30 km from the Mitre peninsula by the Le Maire strait to the southeast of the Isla Grande of Tierra del Fuego (Main Island of Tierra del Fuego). Isla de los Estados occupies a strategically important position between the Antarctic Peninsula and the South American continent providing important palaeoenvironmental information concerning the weather and impact of climate changes that have taken place since the last glaciation. Botanically, the island is situated in the extreme east of the Subantarctic Evergreen Forest that constitutes the world?s southernmost forest, extending down to 56° S only 800 km from the Antarctic Peninsula. The climate changes that occurred in the far south of Patagonia and the Isla Grande of Tierra del Fuego in the recent geological past have been investigated mainly through geomorphological and palaeoecological studies (Coronato et al., 2007). The Beagle Channel (54° 53? S between 66° 30? and 70° W) to the south of Tierra del Fuego is an ancient tectonic valley that was completely filled with ice during the last glacial maximum (LGM, ca. 24 ka B.P.; Rabassa, 2008.). The Beagle glacier originated from the Darwin Mountain Range ice field, receiving tributary glaciers from the internal cirques and valleys of the mountainous branches of both margins of the range. At its maximum extent the ice front was located at Moat Point (120 km to the east of Isla de los Estados), where many moraine arcs can be seen. Judging by the basal ages of the peat bogs found along the Beagle Channel it may be inferred that around 14ka B.P. the ice front had retreated some 100 km to the west of its point of maximum extension. The final retreat of the ice occurred at least around 10 ka B.P., when the first communities of ...